2015
DOI: 10.1039/c5cy00751h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorination of acetylene using supported phosphorus-doped Cu-based catalysts

Abstract: Phosphorus-doped copper catalysts supported on spherical activated carbon (SAC) were prepared using an incipient wetness impregnation technique. The catalysts were characterized by low-temperature N 2 adsorption/desorption, X-ray diffraction (XRD), transmission electron microscopy (TEM), temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS), inductively coupled plasma (ICP), N 2 O pulse titration method and thermogravimetric (TG) technologies. The results indicate that the phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 45 publications
5
42
0
Order By: Relevance
“…In previous studies of numerous metal chlorides and carbon catalytic materials,, activated carbon‐supported AuCl 3 catalyst (AuCl 3 /AC) as a green and efficient non‐mercury catalyst is considered to be most promising alternative to HgCl 2 /AC catalyst for acetylene hydrochlorination ,. Compared with HgCl 2 /AC catalyst, AuCl 3 /AC catalyst exhibits better initial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of numerous metal chlorides and carbon catalytic materials,, activated carbon‐supported AuCl 3 catalyst (AuCl 3 /AC) as a green and efficient non‐mercury catalyst is considered to be most promising alternative to HgCl 2 /AC catalyst for acetylene hydrochlorination ,. Compared with HgCl 2 /AC catalyst, AuCl 3 /AC catalyst exhibits better initial activity.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure a, the acetylene conversion over 10%Sn‐MOF/AC decreased from 93.5% to 52.6% after 40 h. However, the 10%SnCl 2 /AC catalyst was quickly inactivated after 10 h. Although non‐precious metals exhibit lower toxicity and better catalytic properties, metal chloride catalysts exhibit a lower stability . Compared to 10%SnCl 2 /AC and 17%ZIF‐8/SAC, after interacting with o‐phthalic acid, 10%Sn‐MOF/AC revealed a relatively higher stability and activity for the hydrochlorination of acetylene.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Zhang et al . reported that carbon‐supported Cu−P/AC can catalyze the acetylene hydrochlorination with 97.2% acetylene conversion; at same time, the introduction of phosphorus in Cu(II)‐based catalysts can effectively promote the lifetime compare to CuCl 2 /AC . Dai et al .…”
Section: Introductionmentioning
confidence: 96%
“…The energy structure of China's rich coal and lean oil dictates that the production of vinyl chloride monomer (VCM) by acetylene hydrochlorination is the best route for large-scale production of polyvinyl chloride (PVC). [1] Considerable research efforts have been devoted to developing mercury-free catalysts, such as AC-supported AuCl 3 , [2][3][4] PdCl 2 , [5][6][7] RuCl 3 , [8,9] and CuCl 2 [10,11] to replace conventional Hg-based catalysts in the hydrochlorination of acetylene because of the mercuric chloride lost from the catalyst can disperse into the environment, which will seriously endanger human health. Hutchings and coworkers showed that Au catalysts are the most promising mercury-free catalysts.…”
Section: Introductionmentioning
confidence: 99%